Pemetaan Percepatan Getaran Tanah Maksimum, Indeks Kerentanan Seismik Tanah, Ground Shear Strain, dan Ketebalan Lapisan Sedimen Untuk Mitigasi Bencana Gempabumi Di Kabupaten Bengkulu Utara - , BUDI HARLIANTO; , Dr. H. Wahyudi, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Microtremor research has been conducted in North Bengkulu on May 25 until May 28, 2012. This study was conducted to map the distribution of the Peak Ground Acceleration values (PGA), Seismic vulnerability index (Kg), ground shear strain (Î³), and the thickness of the sediment layer (h), which indicate the level of vulnerability of a region to the earthquake hazard. Data this research using three-component seismometer type DS-4A at 29 measurement points data. The method to analyze data using Horizontal to Vertical Spectral Ratio (HVSR), to calculation PGA in ground surface layer value using Kanai empirical equations for earthquake event September 12, 2007 with a moment magnitude of 8.5. The results of this research shows us that, in North Bengkulu district the distribution of PGA in ground surface layer values ranged from 152 to 674 gal, distribution of seismic vulnerability index value (Kg) ranged from 0.3 to 15.5, distribution of ground shear strain values (Î³) ranged from 4,4x10-5 to 2,5x10-3, and sediment layer thickness (h) ranged from 6 to 127 meters. PGA in ground surface layer values, Kg, Î³ are low and h is thin in commonly the District Napal Putih, Argamakmur, Batik Nau, and Kerkap, whichs suffered the minor damage levels. While the high value of PGA in ground surface layer, Kg, Î³ and the thick of sediment layer (h) is commonly contained in District of Lais, Air Napal, Ketahun, and Putri Hijau, which suffered the heavy damage level.